Modern Day Slavery in Your Supply Chain - Walden, Joseph L. (Advances in Social Sciences Research Journal, 2023)
Modern day slavery is a huge problem in supply chains. Estimates place the number of workers living in slavery conditions between 17-21 million worldwide. This problem is growing rather than shrinking even though countries have laws that prevent slave labor and some countries and states have laws that require reporting on audits of their supply chains. Why do we have this problem and what can we do to fix it? This paper addresses the issue and some recommendations to fix this global problem.